Manifestations of dyslexia and dyscalculia (2013)
This study examined the prevalence of dyslexia and dyscalculia among persons with academic deficits in English Language and Mathematics in public primary schools in Ibadan metropolis. A correlational survey study, sampling 477 pupils who were between the ages of eight and 12 years, and in 4th and 5th grades with the use of four research instruments- the Myklebust Pupil Rating Scale (MPRS), the Slosson Intelligence Test- Revised Third Edition (SIT-R3), the Test of Pupil Reading Abilities Test (TPRA) and the Mathematical Abilities Test (MAT) was adopted. It was discovered that dyslexia and dyscalculia were prevalent among pupils with academic deficits in English Language and Mathematics, and that pupils with both dyslexia and dyscalculia are in the larger percentage.- It was also discovered that learning disabilities, dyslexia and dyscalculia were not peculiar to any gender. Persons with academic deficits in English language and mathematics should be screened for either dyslexia or dyscalculia, even both. Also, they should be taught according to a carefully developed Individualized Education Plan